Analysis of motor learning task in children with intellectual disability - Jorge Lopes Cavalcante Neto; Érica Alane Silva; Marília Silva Guedes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Children with intellectual disabilities (ID) present cognitive deficits interfering with the motor learning process. Objective: To analyze the motor learning of children with intellectual disability (ID) and compare with typically developing children. Methods: The sample was composed of 20 children of both genders (10 with ID and aged 8.5±1.57 years). The experimental (EG) and control (CG) groups were composed of children with and without ID, respectively. We used a maze task printed on a paper sheet (A4 size). Ten attempts were performed on the first day: five for the acquisition 1 (A1) and five for the acquisition 2 (A2) phase. Five attempts were also performed 48 hours later for the retention phase (RET). Results: The results related to the motor learning phases were lower in the EG compared with CG (p < 0.01). Within-group comparisons showed no significant differences between the outcomes. Children in the EG maintained the score in the A1 and A2 phases and declined in the RET phase, while the CG maintained the same scores over the three phases. Conclusion: Children with ID presented lower performance in the maze task than typically developing children. It seems that motor learning is slower in individuals with ID than controls, and they need more time and repetitions to learn the maze task.